Relationship between distributive justice, procedural justice, and satisfaction after service recovery - Abu Bakar, Siti Zakiah (2018)
This study reflects the relationships between perceived justice which consists of distributive justice and procedural justice, and satisfaction after a service failure.Satisfied customers will translate to ongoing business due to repeat purchase.The platform of the study is e-service. The factors that could alter customers‟ sentiments after failure were identified.These factors will be an important element for service providers to include in designing the recovery process policy.The factors namely distributive justice, procedural justice, and satisfaction were tested. The respondents are customers of e-services and their reaction after an e-service failure and recovery were recorded.Data from a mid-western university in the United States was collected and analyzed.Multiples regression test was carried check the hypotheses.There was a significant interaction effect with distributive justice and procedural justice in predicting satisfaction after service failure.